Conventional and Non-Conventional Applications of β-galactosidases - Vera-Vera, C (Elsevier B.V., 2020)
β-Galactosidase is one of the most important industrial enzymes, that has been used for many decades in the dairy industry. The main application of β-galactosidase is related to the production of low-lactose and lactose-free milk and dairy products, which are now common consumer goods in supermarket shelves. This is a well-established market that is expected to keep on growing as these products become more accessible to mid-income people worldwide. However, a fresh air has come into the β-galactosidase business as non-conventional applications arose in recent decades based on its transgalactosylation activity. This capacity is certainly a major asset for a commodity enzyme that can be used now as a catalyst for the upgrading of readily available and cheap lactose into high added-value glycosides in processes of organic synthesis in tune with green chemistry principles within the framework of sustainability. This is a reflection of a paradigm shift, where enzymes are now being considered as apt catalysts for the synthesis of valuable organic compounds. This article reviews the main applications of β-galactosidase, going from its conventional use related to its hydrolytic activity to the ongoing non-conventional applications in the synthesis of high added-value oligosaccharides based on its transgalactosylation activity. © 2019 Elsevier B.V.